Comparison of the Basal View and a Previously Standardized Cleft Lip Rating Scale. (October 2018) - Klein, Gabriel M.; Dhawan, Arjun; Laskowski, Robert A.; Peredo, Andrew L.; Kelly, Raymond; Gelfand, Mark A.; Khan, Sami U.; Bui, Dui T.; Dagum, Alexandar B.
Objectives: Numerous scales assessing the aesthetics of cleft lip repair exist. Most, including the Asher-McDade scale, use frontal and lateral views, while neglecting a basal view. We believe this view is important for properly assessing the aesthetics of repair. In this study, we evaluate the basal view in comparison to the Asher-McDade scale. Methods: This scale was based on progressive columellar shortening and alar flaring/slumping. A panel of 4 plastic surgeons applied the basal and Asher-McDade scales to pictures of patients with repaired unilateral cleft lip in 56 multiethnic participants aged 5 years to 18 years; images were scored from 1 to 5 (best). Statistical analysis was done via Spearman correlation. Results: Scores from plastic surgeons correlated strongly for each view. There was moderate correlation for the basal view with both nasal form and deviation scores ( P < .05). As expected, there were no strong correlations between the basal view and vermillion border or profile. Discussion: The Asher-McDade scale has been used to evaluate cleft lift repairs but is limited due to its subjective nature. The basal view scale grades these repairs by using a scale of progressive columellar shortening and alar flaring/slumping, which provides an opportunity for quantification and standardization. Our results show that the basal view correlates with the Asher-McDade scale among raters, thus providing an objective and validated measure of cleft lip repair.